The Management Education of the Rural Entrepreneur - Eugen Bruno Stefan (Amfiteatru Economic Journal, 2014)
The Bureau of Social Research, within a strategic EU project– Rural Entrepreneur (2011) – coordinated by the National Foundation of Young Managers, analyzed in 2001 the needs of developing management and consultancy programs in order to improve the knowledge, skills, and managerial behaviour of the small and prospective entrepreneurs from the rural area of Romania. This study has revealed that three quarters of the rural entrepreneurs and over 85% of the prospective entrepreneurs have never been trained in management development. Their managerial education is often poor and usually acquired after starting the business up. The majority does not even consider that a prior training is necessary because business opportunities in the rural area are rare and the access of European funding is difficult. Over 90% of the new businesses fail in the first year. The managerial training programs and entrepreneurial consultancy can significantly reduce this percentage.
Keywords: D03; I21; M12; 330; entrepreneurship; managerial education; business consultancy; rural management